Measurement of Conservation Value of Ancient Buildings from the Perspective of Climate Risk Based on the Entropy Weighting Method - Shen, Xuhao; Luo, Guangrui; Hu, Chuanxia (Transactions on Computer Science and Intelligent Systems Research, 2024)
Modern society is characterized by high levels of human activity and pollution, triggering numerous extreme weather events. This has resulted in numerous disaster losses, and ancient buildings of conservation value are often damaged by extreme weather. To mitigate the crisis caused by the increasingly severe climate risk to the protection of ancient buildings, this paper will measure the level of exposure of ancient buildings to climate risk this paper constructs a comprehensive evaluation index system that includes eight factors affecting the level of architectural protection from the aspects of history and culture, economic and social, and natural environment. On this basis, the Entropy Weighting Method and Delphi Method are used to establish a Building Conservation Model, and the weights of the subjective and objective factors are combined to prioritize the indicators, and the model is used to help regional leaders determine to what extent measures should be taken to protect buildings. In our model, the USA ranked first with a score of 0.116, followed by China with 0.005. This paper will provide a decision-making basis for the units responsible for the conservation of ancient buildings, and help them to identify and prevent climate risks to ancient buildings.